Extending Web applications with 3D features - Bochicchio, M. A.; Longo, A.; Vaira, L. (2011 13th IEEE International Symposium on Web Systems Evolution (WSE), 2011)
3D visual interfaces are effective, attractive, and are considered as a key factor to add value to various software applications improving the overall user experience. The Web is one of the domains where 3D visual interfaces can bring advantages, and the recent integration between 3D and web technologies, driven by html 5 and WebGL, establishes good basis to extend web applications with 3D features. However, much work must be done to promote html 5 and WebGL from the role of enabling technology to the role of solid foundation for enterprice level applications. In this scenario the focus of the paper is on outlining some guidelines and a workflow to add 3D data visualization features to existing Web applications. The paper also discusses the main results we achieved applying these guidelines to two different application fields.